The evaluation of learning mediated by TAC (Docentes 2.0 Journal, 2020)
The present work aims to analyze the assessment instruments for learning mediated by Learning Technologies and the knowledge of a virtual training course for teachers at the primary level in the Province of Buenos Aires, Argentina. The use of the qualitative approach allowed to recover the reflections, thoughts and positioning of the teachers and tutors, as a product of the interaction in the virtual classroom. The evaluation indicators analyzed were content, activities, methodological strategies, evaluation instruments, the role of the students and the role of the tutor. The results obtained from the analysis of the data showed different resources that acted as pedagogical mediators. Regarding the conclusions, the pedagogical value of learning technologies and knowledge as mediators of the learning evaluation process is appreciated.
Keywords: Formative Evaluation; Technology- feedback; Self-appraisal